Is There a Farm-Size Productivity Relationship in African Agriculture? Evidence from Rwanda - Ali, Daniel Ayalew; Deininger, Klaus (World Bank, Washington, DC, 2014)
Whether the negative relationship between farm size and productivity that is confirmed in a large global literature holds in Africa is of considerable policy relevance. This paper revisits this issue and examines potential causes of the inverse productivity relationship in Rwanda, where policy makers consider land fragmentation and small farm sizes to be key bottlenecks for the growth of the agricultural sector. Nationwide plot-level data from Rwanda point toward a constant returns to scale crop production function and a strong negative relationship between farm size and output per hectare as well as intensity of labor use that is robust across specifications. The inverse relationship continues to hold if profits with family labor valued at shadow wages are used, but disappears if family labor is rather valued at village-level market wage rates. These findings imply that, in Rwanda, labor market imperfections, rather than other unobserved factors, seem to be a key reason for the inverse farm-size productivity relationship.